Time series analysis : forecasting and control - Box, George E. P.; Jenkins, Gwilym M. (San Francisco : Holden-Day, 1970)
Time Series Analysis has served as one of the most influential and prominent works on the subject. It provides a balanced presentation of the tools for modelling and analysing time series and also introduces the latest developments that have occurred in the field over the past decade through applications from areas such as business, finance, and engineering.
Includes index.
Includes bibliographical references: p. 538-542.
lje 21/01/2019
Loans
Keywords: Time-series analysis; Prediction theory; Transfer functions; Feedback control systems